VELOCITY AS A FUNCTION OF STATE IN GR MECHANICS - Abdildin, M. M.; Beiseen, N. A.; Boshkaev, K. A.; Taukenova, A. S. (Recent Contributions to Physics, 2009)
In present work it is shown that representation of velocity as a function of state in GR mechanics together with improved Fock’s first approximation metrics and Euler’s hydrodynamic formula allows solve a relativistic rotational equation of motion unambiguity problem in GR mechanics.